2003
DOI: 10.5713/ajas.2003.655
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance and Carcass Characteristics of Malpura and Mutton Synthetic Lambs Fed Low and High Energy Rations in a Semiarid Region of India

Abstract: Forty eight lambs (24 each of Malpura and Mutton synthetic breeds) were weaned at 90 days of age and divided into two groups. One group of 12 lambs from each of the two breeds was maintained on low energy (52% TDN) and the other group of 12 on high energy (58% TDN) feedlot ration until 6 of the lambs attained 20 kg and the other 6 attained 25 kg live weight in each of the two groups. Daily feed intake and weekly body weights were recorded. Conventional metabolism trials were conducted on the two breeds and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
4
3
1
Order By: Relevance
“…Contrary to this study, Singh et al (2003) found similar percentage of TNEO among lambs fed different rations. Majdoub-Mathlouthi et al (2013) also reported a contradicting result of percentage of testis affected by diet.…”
Section: None Edible Offalcontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to this study, Singh et al (2003) found similar percentage of TNEO among lambs fed different rations. Majdoub-Mathlouthi et al (2013) also reported a contradicting result of percentage of testis affected by diet.…”
Section: None Edible Offalcontrasting
confidence: 99%
“…In agreement with the present study, Singh et al (2003) reported breed effect on percentage of TEO. Further, Macit et al (2002) reported no effect of breed on percentage of head, liver and heart which confirmed the result of the present study.…”
Section: Edible Offalsupporting
confidence: 94%
See 2 more Smart Citations
“…Low genetic potential, poor nutritional status (maintained on scrub vegetation under extensive system without concentrate supplement) and early age slaughter (between 6 months to one year of age) are the main reasons for the low productivity of Indian sheep compared to those in more agriculturally developed countries. For scanty suitable grazing lands in most of the states, the shepherds keep on migrating their flocks over extensive areas within or even in the neighboring states (Singh et al 2003, Karim 2008, Das et al 2008, Girish et al 2012.…”
Section: Resultsmentioning
confidence: 99%